Why are migrant students better off in certain types of educational systems or schools than in others? On the effects of educational systems, school composition, track level, parental background, and country of origin on the achievement of 15-year-old migrant students - Jaap Dronkers; Rolf van der Velden; Allison Dunne (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
The main research question of this paper is the combined estimation of the effects of educational systems, school composition, track level, and country of origin on the educational achievement of 15-year-old migrant students. We focus specifically on the effects of socioeconomic and ethnic background on achievement scores and the extent to which these effects are affected by characteristics of the school, track, or educational system in which these students are enrolled. In doing so, we examine the 'sorting' mechanisms of schools and tracks in highly stratified, moderately stratified, and comprehensive education systems. We use data from the 2006 Programme for International Student Assessment (PISA) wave. Compared with previous research in this area, the paper's main contribution is that we explicitly include the tracks-within-school level as a separate unit of analyses, which leads to less biased results concerning the effects of educational system characteristics. The results highlight the importance of including factors of track level and school composition in the debate surrounding educational inequality of opportunity for students in different education contexts. The findings clearly indicate that the effects of educational system characteristics are flawed if the analysis only uses a country- and a student level and ignores the tracks-within-school level characteristics. From a policy perspective, the most important finding is that educational systems are neither uniformly 'good' nor 'bad', but they can result in different consequences for different migrant groups. Some migrant groups are better off in comprehensive systems, while others are better off in moderately stratified systems.
Keywords: 330